Early Postural Instability in Parkinson’s Disease: A Biomechanical Analysis of the Pull Test - Javier Ricardo Pérez-Sánchez; Francisco Grandas (Parkinson's Disease)
Postural instability in Parkinson’s disease (PD) is commonly assessed by the pull test. This clinical test may be biased by the variability of the pull force applied. Our objective was to study the postural responses elicited by reproducible pull forces in healthy subjects and PD patients at different stages of the disease. We performed a multimodal approach that included a systematic analysis of the pull force needed to reach the backward limit of stability (FBLoS) assessed by mechanically produced forces, the displacements of the center of pressure (CoP) recorded on a force platform, and the latencies and patterns of activation of the stabilizing muscles. Comparisons between groups were performed by univariate and multivariate statistical analyses. Sixty-four healthy subjects and 32 PD patients, 22 Hoehn–Yahr (H–Y) stages I-II and 10 H–Y stage III, were studied. In healthy subjects, FBLoS decreased with aging and was lower in females. Mean (SD) FBLoS was 98.1 (48.9) Newtons (N) in healthy subjects, 70.5 (39.8) N in PD patients H–Y stages I-II, and 37.7 (18.9) N in PD patients H–Y stage III. Compared to healthy subjects and when adjusted for age and gender, PD patients H–Y stages I-II exhibited the following: (a) a reduced FBLoS; (b) larger CoP displacements and higher velocities for the same applied force; and (c) combined ankle and hip strategies elicited by less intense pull forces. All of these abnormalities were more pronounced in H–Y stage III PD patients compared to H–Y stages I-II PD patients. In conclusion, patients in the early stages of PD already exhibit a degree of postural instability due to inefficient postural adjustments, and they can more easily be destabilized by small perturbations than healthy subjects. This balance impairment becomes more pronounced in more advanced PD. In the pull test, pull force to step back should be a variable to consider when testing balance in clinical practice.